Cuantificación y caracterización general del empleo turístico en Uruguay - Silvia Altmark; Karina Larruina (European Regional Science Association (ERSA), 2011)
"QUANTIFICATION AND GENERAL CHARACTERIZATION OF TOURISM EMPLOYMENT IN URUGUAY" Altmark, Silvia, salt@iesta.edu.uy Larruina, Karina, karinalarruina@gmail.com Statistical Institute, Faculty of Economics and Business Administration, UdelaR (University of the Republic) Tourism, a labour intensive activity, plays an important role in the Uruguayan economy, with an estimated weight in the GDP of 6% in 2009. One of the main externalities of tourism is the employment generation, hence the great importance trying to measure it. Despite the importance of this activity in Uruguay, there is no background of indicators that allows quantification of the contribution of tourism in the employment generation in the national economy. The aim of this work is to measure the contribution of tourism activity in the generation of employment in Uruguay between 2006 and 2009. Specifically, to determine the number of working places generated in this activity, to elaborate an indicator of the participation of tourism employment in the economy and to characterize the tourist workforce, applying the conceptual frame provided by the World Tourism Organization (UNWTO) and the Organization for the Cooperation and the Economic Development (OECD). In addition, we analyzed the experiences in measuring tourism employment of different countries, as Spain and Argentina. To determine the typical industries of tourism activity we used the classification of tourist activities adapted for Uruguay in the frame of the project MINTUR-IESTA. The information was obtained of the Continuous Household Survey of the National Institute of Statistics (INE) held since 1968 and from which there are extracted the principal employment statistics of the country. The main result achieved in this paper, as regards the participation of tourism employment, indicates that it remained around 8% between 2006 and 2009. As for the characterization of employment in tourism, in the analyzed period shows a high share of male heads of household, up to 37 years old, who are private employees and make contributions to the national welfare agency, "Banco de Previsión Social" (BPS).
Keywords: 330